Operacjonalizacja mobbingu w kontekście badań międzykulturowych - Durniat, Katarzyna; Kulczycka, Agnieszka (Mobbing operationalization in view of cross-cultural research, 2006)
The aim of this paper is to present the problem of searching for the adjusted methodology for mobbing detection in Polish environment. It is done in view of cross-cultural research. The concept of mobbing is showed here as a working environment pathology of international meaning. Nevertheless the comparisons among the results of the research conducted in Poland and other European countries lead to the conclusion that mobbing in Poland has its strong cultural connotations. This fact cannot be neglected in both theoretical and empirical studies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 458-467